Threat-responsiveness and the decision to obtain free influenza vaccinations among the older adults in Taiwan - Liu Chi-Mei; Li Ying-Chun (BMC, 2009)
Abstract Background Although older adults are encouraged by government agencies to receive influenza vaccinations, many do not obtain them. In Taiwan, where universal health care coverage has significantly reduced the barriers of access to care, the health care system has provided free influenza vaccinations for people 65 years or older since 2001. Nevertheless, the numbers of people who use this service are much fewer than expected. The aim of this study was to explore major factors that might affect the decision to receive influenza vaccinations among older adults in Taiwan. Methods Using national representative health insurance medical claims from the National Health Insurance Research Database between 2002 and 2004, we investigated the role of threat-responsiveness, represented by prior vaccinations and prior physician visits for flu-like respiratory conditions, in the decisions of older adults to obtain vaccinations in Taiwan. Results Among the sample of 23,023 older adults, the overall yearly vaccination rates in this study were 38.6%, 44.3% and 39.3% for 2002, 2003, and 2004, respectively. Adjusting for covariates of individual and health care facility characteristics, the multivariate logistic regression revealed that older adults who had had prior vaccinations were ten times more likely to be vaccinated during the following influenza season than those who had not (OR = 10.22, 95%CI: 9.82-10.64). The greater the frequency of prior physician visits for flu-like respiratory conditions, the greater the likelihood that one would decide to be vaccinated. Visits during prior interim (non-epidemic) season exerted a stronger positive influence than prior influenza season on this likelihood (OR = 1.59, 95% CI: 1.46-1.73 vs. OR = 1.11 95% CI: 1.01-1.22, respectively). Conclusion Threat-responsiveness, or perceived risk, greatly influences influenza vaccination rates among the older adults in Taiwan. These findings can be used to help design public health campaigns to increase the influenza vaccination rate in this vulnerable group of citizens. Particularly, older adults who never had influenza vaccinations can be identified, educated, and encouraged to participate.